Adherence to anti-hypertensive treatment: an analysis using the Morisky-Green Test - Eid, Letícia Palota (2013)
doi: 10.5216/ree.v15i2.15599 - http://dx.doi.org/10.5216/ree.v15i2.15599. ABSTRACT Considering that treatment adherence is a challenge in controlling systemic hypertension (SH), the objective of this study was to characterize subjects according to sociodemographic and economic variables and assess the adherence level using the Morisky-Green Test. This descriptive, cross-sectional, quantitative study was performed with 90 hypertensive individuals at a Health Center. Data collection was performed using the Morisky-Green test (MGT). Results show that 63.0% of the sample were women, with a mean age of 66 years, 72.2% of which did not adhere to the drug treatment, thus corroborating with current research on adherence. In conclusion, this study can provide support for health care interventions to patients with SH, aiming to increase adherence rates and improve quality of life. Descriptors: Hypertension; Medication Adherence; Nursing.